Science, Technology, Engineering and Mathematics (STEM) Education in the United States of America and Saudi Arabia: A Comparative Study - Al-Otaibi, Saud Mutlaq (Journal of Educational and Psychological Sciences, 2023)
This study sought to compare between STEM Education in the USA and STEM Education in the KSA considering the affecting forces and factors, and to identify the similarities and differences between both USA and KSA; the Researcher used the descriptive comparative approach in its three steps, namely: description, interpretation, and comparison; the Researcher selected two (2) documents as an intended sample of STEM Education Policy in the USA. Those two documents are: Federal Strategic Plan for STEM Education (2013) and the American Strategy for STEM Education (2018). The study consists of three sections, the first section deals with the theoretical framework and previous studies, while the second section includes a comparison between STEM Education in the USA and the KSA, and the third section reviews findings, recommendations, and proposals of the study. The study made several findings, the most important of which is: lack of STEM Education Policy in the KSA, while it is evident that the USA presidents have been interested in the STEM Education as an important educational reform to prepare the children for the global economy in the 21st century, and that the STEM Education in the USA is strongly associated with the geographical, demographic, social, economic and political factors. Based on the study findings, the researcher recommends spreading the STEM Education culture in the educational and community circles and re-designing the curricular activities to ensure integration between science, technology, engineering, and mathematics (STEM). Moreover, the Researcher proposes conducting a study to develop the STEM teacher training programs.